2015
DOI: 10.1016/j.celrep.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2 Regulates Cardiac Response to Stress by Inhibiting MST1

Abstract: Summary The mTOR and Hippo pathways have recently emerged as the major signaling transduction cascades regulating organ size and cellular homeostasis. However, direct crosstalk between two pathways is yet to be determined. Here we demonstrate that mTORC2 is a direct negative regulator of the MST1 kinase, a key component of the Hippo pathway. mTORC2 phosphorylates MST1 at serine 438 in the SARAH domain, thereby reducing its homodimerization and activity. We found that Rictor/mTORC2 preserves cardiac structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 51 publications
7
81
0
Order By: Relevance
“…Rapamycin, a drug that strongly inhibits mTORC1 but to a lesser level mTORC2, blunts cardiac hypertrophy development in response to pressure overload 44 and improves cardiac function in mice with decompensated hypertrophy 45 . It was recently reported that cardiac-specific mTORC2 disruption through Rictor deletion leads to impaired cardiac growth and response to pressure overload, cardiac dilation and cardiac dysfunction 46 , features that we similarly found after Stim1 silencing.…”
Section: Discussionsupporting
confidence: 79%
“…Rapamycin, a drug that strongly inhibits mTORC1 but to a lesser level mTORC2, blunts cardiac hypertrophy development in response to pressure overload 44 and improves cardiac function in mice with decompensated hypertrophy 45 . It was recently reported that cardiac-specific mTORC2 disruption through Rictor deletion leads to impaired cardiac growth and response to pressure overload, cardiac dilation and cardiac dysfunction 46 , features that we similarly found after Stim1 silencing.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, the nutrient-sensing kinases salt-induced kinase 2 and kinase 3 phosphorylate Sav at Ser413 to promote Yki target gene expression (Wehr et al 2013). Both mTORC1 and mTORC2 are reported to positively regulate YAP in perivascular epithelioid cell tumors and glioblastomas (Liang et al 2014;Artinian et al 2015;Sciarretta et al 2015). It is worth noting that mTORC1 is highly sensitive to nutrient availability and cellular energy status.…”
Section: Stress Signalsmentioning
confidence: 99%
“…Some studies suggest that Mst1/Mst2 homodimerization is required for autophosphorylation and activation of these kinases [8, 15, 16] while others indicate that homodimer formation is not required for its activity [8, 17]. In addition to forming homodimers, Mst1 and Mst2 have also been shown to heterodimerize with other SARAH domain containing proteins, such as, RASSF family of proteins [8, 1820].…”
Section: Resultsmentioning
confidence: 99%